2012
DOI: 10.1136/bmjopen-2012-001370
|View full text |Cite
|
Sign up to set email alerts
|

Do ω-3 or other fatty acids influence the development of ‘growing pains’? A prebirth cohort study

Abstract: ObjectivesTo assess whether the prevalence of growing pains varies with indicators of fatty acid exposure. Growing pains (limb pains of no obvious explanation) have been shown to be strongly linked to a family history of arthritis, and are thought to predict an increased risk of the development of arthritis in adulthood. Much has been made of the possibility of fatty acids, particularly the ω-3 fatty acids, playing a preventive role in the development of arthritis, but little research has been undertaken to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In a Mediterranean population of children 3–12 years old the frequency of the disorder was 24.5% [4], while Oster found that 15% of school children have occasional limb pain [35]. In a very large British cohort study, but without applying Peterson’s criteria for GP assessment, the referred prevalence was 21.4% [14]. Overall, their prevalence varies from 2.6% to 49.4% [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Mediterranean population of children 3–12 years old the frequency of the disorder was 24.5% [4], while Oster found that 15% of school children have occasional limb pain [35]. In a very large British cohort study, but without applying Peterson’s criteria for GP assessment, the referred prevalence was 21.4% [14]. Overall, their prevalence varies from 2.6% to 49.4% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that very low birth weight infants had reduced bone mass at ages 5 to 10 years, even after adjustment for height, lean mass, or bone area [47], whereas in the same study, short gestation period was correlated with unfavorable skeletal health among prepubertal boys [47]. Predicated on the concept that vitamin D deficiency [12,13,14,15,16] and BMD [8] are key factors for the development of GPs, further research may reveal if the implication of perinatal risk factors in the bone metabolism process results in the onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…British cohort study, but without applying Peterson's criteria for GPs assessment, the referred prevalence was 21.4% [13]. Overall, their prevalence varies from 2.6 to 49.4% [33].…”
Section: Gps In Dizygotic Twinsmentioning
confidence: 91%
“…Furthermore, a twin family survey [10] provided evidence that GPs appear genetic susceptibility and present genetic association with Restless Leg Syndrome. Currently, many studies focus on the correlation of Growing pains with bone density [7] and with factors affecting paediatric bone metabolism regarding serum levels of vitamin D, or calcium [7] and ω-3 fatty acids intake [11][12][13][14][15]. The bone strength theory is based on the observation that the tibial bone density in children with GPs, as it was measured by quantitive ultrasound, was significantly reduced compared to healthy children [7].…”
mentioning
confidence: 99%